DIET COMPOSITION OF ANOA (Buballus sp.) STUDIED USING DIRECT OBSERVATION AND DUNG ANALYSIS METHOD IN THEIR HABITAT - Pujaningsih, R.I.; Sutrisno, C.I.; Supriondho, Y.; Malik, A.; Djuwantoko, D.; Pudyatmoko, S.; Amir, M.A.; Aryanto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
Anoa are fully protected under Indonesian Law since 1931 (Law of Protection of Wild Animals 1931, no134). Increasing law enforcement regarding hunting as well as promoting awareness of the Anoas uniquethreatened the existence of conservation measures. The modern concept of conservation based on thesustainability utilization, and therefore the knowledge of the Anoa preference in feeding to support thesustainability conservation should be studied. In the present study, the combination of direct observationmethods which was done in the Lore Lindu National Park in Toro village at District Kulawi, Central Sulawesiand the epidermal analysis method which was carried out to Anoa’s dung were aimed to identify the vegetationspreferred by Anoa in their habitat. The result showed 28 species of vegetations was used as feed by Anoaon in situ area. According to its percentage, the first ten were Freycinetia insignis Blume (17%), Microlepiatodayensis Christ (8.9%), Disoxylum sp (8.6%), Lasianthus clementis Merr (7.7%), Clusia sp (7.5%),Schleria sp (6%), Podocarpus imbricatus (5.4%), Smilax leucophylla (5.1%), Elastostema sp (4.2%),and Garcinia sp (3.8%), respectively. Furthermore, it can be concluded that Anoa was eat more leafs andshrubs/bushes (each 24%, respectively) compared to flowers (18%), fruits (12%), shoots (8%), grasses,tubers, young grooves (each 4%, respectively) and moss (2%). Nutritionally, Anoa consumed 8.8% proteinand 25.6% crude fiber.